2019
DOI: 10.3390/app9142936
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of PM2.5 Air Pollution in Mexico City: Spatial Analysis with Land-Use Regression Model

Abstract: Featured Application: Modeling the spatial distribution of PM 2.5 with personal monitors and an LUR approach may be useful for local authorities to make accountable public policy decisions.Abstract: In this study, the spatial distribution of PM 2.5 air pollution in Mexico City from 37 personal exposures was modeled. Meteorological, demographic, geographic, and social data were also included. Geographic information systems (GIS), spatial analysis, and Land-Use Regression (LUR) were used to generate the final pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
(60 reference statements)
1
5
0
2
Order By: Relevance
“…Wang et al also found that PD exerts a remarkable effect on PM 2.5 concentrations [ 18 ]. Hinojosa et al indicated that population was correlated with PM 2.5 concentration using data from Mexico City [ 47 ]. The results of the current study demonstrate that anthropogenic emissions are the key factors leading to significant increases in PM 2.5 concentrations in North China between 2000 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al also found that PD exerts a remarkable effect on PM 2.5 concentrations [ 18 ]. Hinojosa et al indicated that population was correlated with PM 2.5 concentration using data from Mexico City [ 47 ]. The results of the current study demonstrate that anthropogenic emissions are the key factors leading to significant increases in PM 2.5 concentrations in North China between 2000 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…De igual forma nuestros hallazgos coinciden con lo descrito por Hinojosa et al, (2019), en un estudio realizado en la ciudad de México a partir de 37 exposiciones personales. Por lo contrario, en la estación RF1 se logró identificar uno de los valores medios más altos (10.82 µg/m 3 ), lo que indica que existe contaminación a causa de estas partículas por lo que son motivo de preocupación debido a su alta dimensión, así como a sus características fisicoquímicas.…”
Section: Discussionunclassified
“…Cabe indicar también que el PM 2.5 µm y 10 µm son partículas que al ingresar a la caja torácica causan efectos agudos y crónicos en la salud de las personas (Salinas, 2012). Por ello vale la pena mostrar que más del 80% de la población en países en vías de desarrollo están expuestos a niveles peligrosos de calidad del aire, que con frecuencia los contaminantes exceden los límites máximos permisibles (Hinojosa et al, 2019).…”
Section: Introductionunclassified
“…The development of analytical approaches to determine and assess environmental pollution data with the best spatiotemporal granularity is key in the design and implementation of proper intervention policy, for example, regarding urbanization process, over-population, personal monitors, indoor environments, vehicle fleet, peak hours, and green areas in the city, among others (33). The PAHO Regional Plan on Urban Air Quality and Health 2000-2009 has proposed efficient systems for air pollution health impact monitoring.…”
Section: Intervention Policy and Assessmentmentioning
confidence: 99%